ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN EKONOMI SEKTOR PERTANIAN DI KALIMANTAN BARAT - B01107067, SUMIATI (Jurnal Pembangunan dan Pemerataan, 2016)
The aim of this study was to determine the effect indicators (investment, labor, agricultural area) the economic growth of the agricultural sector in West Kalimantan. As well as how the economic growth of agriculture in West Kalimantan. The methodology used in this study is a model of panel data regression analysis (cross section and time series), by observing the data as much as 70 in West Kalimantan, During the period 2006 to 2010. The processing of data using computer program EVIEWS. This research was conducted in the province of West Kalimantan, using secondary data in the form of a written report in the form of data that is investment data, labor and agricultural area in West Kalimantan Province 2006-2010. Based on the results of calculation test Hausman test, regression analysis and various tests that have been done show that investment, labor, agricultural land is a positive-negative and significant effect on economic growth in the agricultural sector in West Kalimantan. Indicators supporting economic growth in the agricultural sector is the most dominant investment, while the role of population growth and a smaller land area. Keywords: agricultural investment, agricultural laborers, agricultural land, economic growth in the agricultural sector.